Structural and optical properties of compensated microcrystalline silicon films - Dussan, A. (2007)
Boron-doped microcrystalline silicon films were deposited in a plasma enhanced chemical vapor deposition (PECVD) system using silane (SiH4) diluted in hydrogen, and diborane (B2H6) as a dopant gas. The effects of the Boron concentration on the optical and structural properties were investigated by the constant-photocurrent method (CPM) and atomic force microscopy (AFM) measurements. The variations in the optical constants (refractive index, absorption coefficient and optical gap) as a function of wavelength were carried out from the optical transmission and CPM spectra. By increasing the doping level, a systematic increase in the absorption coefficient spectra in the low-energy region between 0.7 - 1.2 eV was observed. It was found that the increase of Boron concentration in the samples results in changes of the grain size. Correlations between optical properties and the density of states (DOS) were also studied.